2017
DOI: 10.1128/aem.01326-17
|View full text |Cite
|
Sign up to set email alerts
|

Novel Alphacoronaviruses and Paramyxoviruses Cocirculate with Type 1 and Severe Acute Respiratory System (SARS)-Related Betacoronaviruses in Synanthropic Bats of Luxembourg

Abstract: Several infectious disease outbreaks with high mortality in humans have been attributed to viruses that are thought to have evolved from bat viruses. In this study from Luxembourg, the genetic diversity and epidemiology of paramyxoviruses and coronaviruses shed by the bat species Rhinolophus ferrumequinum and Myotis emarginatus were evaluated. Feces collection (n ϭ 624) was performed longitudinally in a mixed-species colony in 2015 and 2016. In addition, feces (n ϭ 254) were collected cross-sectionally from si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 77 publications
0
34
0
Order By: Relevance
“…In 2005, the discovery of novel CoVs related to human SARS-CoVs in Chinese horseshoe bats (genus Rhinolophus), named SARS-related coronaviruses (SARSr-CoVs), provided new clue that bats may be the natural host for SARS-CoV (Lau et al, 2005;Li et al, 2005). Since then, genetically diverse SARSr-CoVs have been discovered in Asia, Europe, and Africa, including China, South Korea, Thailand, Bulgaria, Slovenia, Italy, Luxembourg, Nigeria, and Kenya (Balboni et al, 2012b;Drexler et al, 2010;He et al, 2014;Lau et al, 2010;Lau et al, 2005;Li et al, 2005;Pauly et al, 2017;Ren et al, 2006;Rihtaric et al, 2010;Yang et al, 2013;Yuan et al, 2010). Importantly, it was reported that some bat SARSr-CoVs were able to use angiotensin converting enzyme II (ACE2) from humans, civets and Chinese horseshoe bats as a receptor originated from Chinese horseshoe bats and suggesting that these SARSr-CoVs had the ability to infect humans immediately without other intermediate hosts.…”
Section: Discovery Of Bat Sars-related Coronaviruses (Sarsr-covs)mentioning
confidence: 99%
“…In 2005, the discovery of novel CoVs related to human SARS-CoVs in Chinese horseshoe bats (genus Rhinolophus), named SARS-related coronaviruses (SARSr-CoVs), provided new clue that bats may be the natural host for SARS-CoV (Lau et al, 2005;Li et al, 2005). Since then, genetically diverse SARSr-CoVs have been discovered in Asia, Europe, and Africa, including China, South Korea, Thailand, Bulgaria, Slovenia, Italy, Luxembourg, Nigeria, and Kenya (Balboni et al, 2012b;Drexler et al, 2010;He et al, 2014;Lau et al, 2010;Lau et al, 2005;Li et al, 2005;Pauly et al, 2017;Ren et al, 2006;Rihtaric et al, 2010;Yang et al, 2013;Yuan et al, 2010). Importantly, it was reported that some bat SARSr-CoVs were able to use angiotensin converting enzyme II (ACE2) from humans, civets and Chinese horseshoe bats as a receptor originated from Chinese horseshoe bats and suggesting that these SARSr-CoVs had the ability to infect humans immediately without other intermediate hosts.…”
Section: Discovery Of Bat Sars-related Coronaviruses (Sarsr-covs)mentioning
confidence: 99%
“…However, the Beilong virus was discovered on human kidney cell lines and neutralising antibodies against J virus have been detected in rodents, pigs and humans (Audsley et al, 2016). In addition, bat viruses belonging to the related-Jeilongvirus genus were widely detected in China and more recently in Luxembourg in Europe (Pauly et al, 2017). Altogether, these data highlight the need for further studies on the zoonotic potential of these viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Several alpha and beta-CoVs have been described worldwide in different bat species (e.g. [9][10][11][12][13][14][15][16][17]). From the first report in China, Rhinolophus species have been specifically associated with SARS-like CoVs [18][19][20], belonging to the lineage b of beta-CoV genus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ever-increasing attention paid to bat-associated pathogens, has led to the discovery of numerous novel and yet unclassified PMV, revealing an unexpected genetic diversity in the Paramyxovirinae subfamily [36]. PMV identification has been reported in only few studies in insectivorous bats in Europe from Germany, Bulgaria, Romania and Luxembourg, with none of the novel viruses closely related with highly or human pathogenic paramyxoviruses [16,17,27,36].…”
Section: Introductionmentioning
confidence: 99%